2017
DOI: 10.1039/c6sc03438a
|View full text |Cite
|
Sign up to set email alerts
|

Insights into ClpXP proteolysis: heterooligomerization and partial deactivation enhance chaperone affinity and substrate turnover in Listeria monocytogenes

Abstract: Caseinolytic protease from Listeria exploits two paths of proteolytic stimulation: heterooligomerization and partial inhibitor binding both enhance ClpX chaperone affinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 34 publications
4
23
0
2
Order By: Relevance
“…[15,17] All our efforts to directly quantify the interaction between ClpX and ClpP by isothermal titration calorimetry (ITC) or surface plasmon resonance (SPR) failed. Thus far,d etermining apparent dissociation constants by activity-based assays has been the standard procedure for ClpP complexes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[15,17] All our efforts to directly quantify the interaction between ClpX and ClpP by isothermal titration calorimetry (ITC) or surface plasmon resonance (SPR) failed. Thus far,d etermining apparent dissociation constants by activity-based assays has been the standard procedure for ClpP complexes.…”
mentioning
confidence: 99%
“…[14] This again highlights the conformational control of ClpX over the catalytic activity of ClpP.Ofnote,asimilar small-molecule-induced enhancement solely of proteolysis was previously described for the ClpXP2 complex from Listeria monocytogenes. [15] As binding of compounds to ClpP can either retain the tetradecameric state or induce disassembly into heptameric species,wedetermined the oligomeric state of the full ClpXP complex upon incubation with phenyl esters.Analytical sizeexclusion chromatography (SEC) with ClpXP composed of an ATP-hydrolysis-deficient ClpX(E183Q) mutant (to facilitate stable complex assembly) [16] revealed that the strongly activating compounds 49 and 50 retain the native complex stoichiometry,n amely ClpX 12 P 14 (Figure S4 a, c). In contrast, an unprecedented peak corresponding to amolecular weight of about 400 kDa was detected after incubation with saturating concentrations of inhibitor 9 (Figure 3a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[15,17] Alle Versuche,d ie Interaktion von ClpX und ClpP direkt durch isotherme Titrationskalorimetrie (ITC) oder Oberflächenplasmonenreso-nanz (SPR) zu bestimmen, schlugen fehl. Bisher wurden fürC lpP-Komplexe standardmäßig apparente Dissoziationskonstanten mittels aktivitätsbasierter Assays bestimmt.…”
unclassified
“…[13] Dementsprechend sind b-Lactone mit Alkylketten unterschiedlicher Länge [6,13] und fluorogene Peptide mit der nichtnatürlichen (S)-2-Aminooctansäure (2-Aoc) in P1-Position [11] Verbindungen wurde bereits fürd en ClpXP2-Komplex aus Listeria monocytogenes beschrieben. [15] Da die Bindung von Inhibitoren an ClpP entweder die tetradekamere Stçchiometrie erhalten oder den Zerfall in Heptamer-Spezies auslçsen kann, wurde der oligomere Zustand des ClpXP-Komplexes nach Inkubation mit Phenylestern untersucht. Analytische Grçßenausschluss-Chromatographie (SEC) von ClpXP,d as eine ATP-Hydrolyse-defiziente ClpX(E183Q)-Mutante enthielt (um eine stabile Komplexanordnung zu gewährleisten), [16] ClpP-Einheit durch den Zerfall des ClpXP-Komplexes.…”
unclassified